2015
DOI: 10.1017/s1755048315000607
|View full text |Cite
|
Sign up to set email alerts
|

Love Thy Neighbor? Relationships between Religion and Racial Intolerance in Europe

Abstract: Abstract:This article examines relationships between religion and racial intolerance across 47 countries by applying multi-level modeling to European survey data and is the first in-depth analysis of moderation of these relationships by European national contexts. The analysis distinguishes a believing, belonging, and practice-dimension of religiosity. The results yield little evidence of a link between denominational belonging, religious practice, and racial intolerance. The religiosity dimension that matters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 72 publications
1
12
0
8
Order By: Relevance
“…The fact, however, is that the nativist, often islamophobic Christians, might be frequent church-goers. In another article, Doebler finds that holding to what is termed "fundamentalist faith" makes one more likely to be intolerant towards immigrant or national minorities, termed "racially intolerant" (Doebler 2015). This finding should not be read to imply that fundamentalist religious views necessarily go together with skeptical view towards immigrants, but there is a higher likelihood that they do.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact, however, is that the nativist, often islamophobic Christians, might be frequent church-goers. In another article, Doebler finds that holding to what is termed "fundamentalist faith" makes one more likely to be intolerant towards immigrant or national minorities, termed "racially intolerant" (Doebler 2015). This finding should not be read to imply that fundamentalist religious views necessarily go together with skeptical view towards immigrants, but there is a higher likelihood that they do.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, the Norwegian Election Programme's survey from 2013 has found that the majority of the 40% who support the statement "We should emphasize a society where Christian values play a greater role" do not themselves report to be believing and/or practicing (Nilsen 2017; see also Ribberink et al 2017;Doebler 2015Doebler , 2014. The terms "emphasize" and "greater role" as applied in the 2013 survey do imply an active endorsement.…”
Section: Recent Surveys On Church Adherence and Views On Immigrationmentioning
confidence: 99%
“…Nos estudos sobre a caracterização da intolerância religiosa foram apresentados diversos aspectos como, níveis e tipos de intolerâncias entendidas como crenças opressivas, afirmando que interferem na construção subjetiva dos sujeitos estudados, sobre aspectos de sexismo, racismo, preconceito sexual, ageísmo, classismo e intolerância religiosa em si (Allport & Ross, 1967;Eisinga et al, 1999;Aosved & Long, 2006;Aosved, Long & Voller, 2009;Doebler, 2015); questões de identidade, diferença, preconceito e religião, levados a apreciação de Tribunais em busca desses posicionamentos sobre a intolerância (Du plessis, 2009;Benson, 2013) e caracterização por meio de estudos teóricos de obras literárias (Beneke & Grenda, 2011;Sorkin, 2017). Nascimento (2015) apresentou uma distinção particularizada da intolerância religiosa contra povos e comunidades de matriz africana brasileira, reportando-se a obra literária e televisiva "Tenda dos Milagres", que retratou o contexto religioso do Candomblé na Bahia, apresentando narrativas de religiosos sobre suas experiências intolerantes que ilustram contextos de sofrimentos psíquicos cotidianos motivados pela discriminação e estigma social, e rejeição familiar, gerando tristeza e revolta nos religiosos.…”
Section: Conteúdosunclassified
“…Os estudos sobre a intolerância religiosa como conflito político, religião e identidade religiosa destacaram a necessidade de aprimoramento das leis e da consciência de grupos étnicos minoritários e, de problematizar a compreensão conceitual sobre religião e identidade africana (Osborn, 2014;Sanni, 2016 (Du plessis, 2009;Doebler, 2015;Ikram, 2016;Mccleary-gaddy & Miller, 2019).…”
Section: Conteúdosunclassified
“…B. gegenüber Homosexuellen) befördern, andere hingegen (z. B. gegenüber Migrant*innen) abmildern kann (Doebler 2015;Rowatt et al 2009;. Das verweist nochmals auf die Relevanz, möglichst spezifisch und differenziert vorzugehen.…”
Section: Diskussion Der Ergebnisseunclassified